Change in geometric entropy with repeated ascents in rock climbing - Watts, P. B.; Espana-Romero, V.; Ostrowski, M. L.; Jensen, R. L. (Sports Biomechanics, 2021)
Lower geometric entropy (GE) could represent more economical movement in rock climbing. Repetition of a climbing route decreases energy expenditure (EE), however, association with changes in GE has not been studied. The purpose of this study was to observe changes in GE with repetition of a climbing route relative to changes in EE. Nine climbers completed nine ascents each, one week apart, on an indoor climbing structure. Digital video was recorded at 30 Hz and a marker point was digitised as an estimate of a climber's centre of mass position (CME). The displacement of CME was expressed as the length of the line of motion (LM). GE was calculated as ln((2 x LM)/CH)) where CH is the value of the convex hull about the LM. Indirect energy expenditure (EECLM) was calculated from expired air by the Weir method. Data were analysed for ascents 1 (A1), 3 (A3), 6 (A6) and 9 (A9) and compared via repeated measures ANOVA. GE was significantly different for A1 vs A6 and A9 (p < 0.05) and not different for other comparisons. GE was correlated with EECLM; r = 0.67 (p < 0.01). Climbers reduce geometric entropy with route familiarity and the lower entropy may be associated with lower energy expenditure.